Identifikasi Telur Cacing pada Saluran Pencernaan Satwa Liar yang Dipelihara Masyarakat di Manokwari, Papua Barat - Nurhayati, Dwi; Baaka, Alnita; Pattiselanno, Freddy (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Investment of parasitic worms of captive wildlife was an impact on their health condition. This study was conducted to determine the intensity of parasitic worm infection in wild animals kept by communities in Manokwari, West Papua. The Natif method was used, by centrifuge of 20 birds and 20 mammals (Kangaroo and Deer) faeces collected from the sites. Sampling was carried out from October to November 2016. The analysis of collected faecal samples showed that bird species were not indicated (negatively infected by worm). In mammals, Nematodes and cestodes were found. Identification of existing findings showed that 3 (three) types of worm eggs were found, namely Taenia sp in kangaroos (Macropodidae), Ascaris sp (berembrio), and stronyle sp in deer (Cervus timorensis). The highest parasites intensity was stronyle sp (10 worm eggs) and the lowest intensity was Ascaris sp (3 worm eggs) .The rate of infection and investment of parasitic worm eggs in wild animals in Manokwari was categorised relatively low.